Partitioning the Uncertainty of Ensemble Projections of Global Glacier Mass Change. Issue 7 (6th July 2020) - Marzeion, Ben; Hock, Regine; Anderson, Brian; Bliss, Andrew; Champollion, Nicolas; Fujita, Koji; Huss, Matthias; Immerzeel, Walter W.; Kraaijenbrink, Philip; Malles, Jan‐Hendrik; Maussion, Fabien; Radić, Valentina; et al.
Abstract: Glacier mass loss is recognized as a major contributor to current sea level rise. However, large uncertainties remain in projections of glacier mass loss on global and regional scales. We present an ensemble of 288 glacier mass and area change projections for the 21st century based on 11 glacier models using up to 10 general circulation models and four Representative Concentration Pathways (RCPs) as boundary conditions. We partition the total uncertainty into the individual contributions caused by glacier models, general circulation models, RCPs, and natural variability. We find that emission scenario uncertainty is growing throughout the 21st century and is the largest source of uncertainty by 2100. The relative importance of glacier model uncertainty decreases over time, but it is the greatest source of uncertainty until the middle of this century. The projection uncertainty associated with natural variability is small on the global scale but can be large on regional scales. The projected global mass loss by 2100 relative to 2015 (79 ± 56 mm sea level equivalent for RCP2.6, 159 ± 86 mm sea level equivalent for RCP8.5) is lower than, but well within, the uncertainty range of previous projections. Plain Language Summary: Melting glaciers (outside the large ice sheets in Greenland and Antarctica) contribute strongly to rising sea level and are expected to continue to do so throughout this century. However, the amount of future sea level rise from glaciers is not well known. One of the causes for uncertainty is the lack of knowledge of future greenhouse gas emissions. This uncertainty is growing steadily during the 21st century and constitutes the most important uncertainty by 2100. Another cause of uncertainty are the glacier models themselves, since they rely on approximations and simplifications of complex glacier processes. This uncertainty is very important until the middle of the 21st century, but less important in the second half of the 21st century. Overall, glaciers will lose around 18 % of their ice mass in a low‐emission scenario, or around 36 % in a high‐emission scenario, contributing roughly 79 or 159 mm to sea level rise by 2100. Key Points: Glacier melt will contribute between 79 ± 56 (RCP2.6) and 159 ± 86 mm (RCP8.5) to sea level rise during 2015–2100 Until the mid‐21st century, disagreement between glacier models dominates the uncertainty At the end of the 21st century, differing emission pathway choices made by human societies dominate the uncertainty